MEASURING FACTORS AFFECTING EARNINGS MANAGEMENT WITH A FIXED EFFECT MODEL ON MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2015-2019 PERIOD - F Firdaus, Venus; Amdani, Amdani (Dinasti Publisher, 2022)
This study aims to determine the effect of institutional ownership, profitability, and leverage on profit management in manufacturing companies in the consumer goods industry sector listed on the IDX for the 2015-2019 period. The variables of this study consist of institutional ownership mechanisms, profitability, leverage, profit management. The population of this study was 56 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in the period 2015-2019. The sampling technique in this study used the purposive sampling method. The sample that has been determined is selected by 20 companies that can be presented with research during 2015 to 2019. In this study, panel data and secondary data obtained from the Indonesia Stock Exchange (IDX) were processed with eviews 9. The results of the research on the mechanism of institutional ownership, profitability, and leverage jointly affect the profit management of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2015-2019 period. This research is expected to be a consideration so that it is not only focused on information on profits and company financial ratios, but investors and creditors can be more careful in assessing the company's condition to be appropriate in making investment decisions and providing funding.